Present distribution (Holocene) of the ground beetle Pelmatellus columbianus in Ecuador - Sofia Isabel Munoz-Tobar (PANGAEA, 2018)
This dataset contains raster grids in TIFF format describing the present distribution of Pelmatellus columbianus in continental Ecuador. The spatial resolution is 2.5 m x 2.5 m.